A framework for optimization of diffusion‐weighted MRI protocols for large field‐of‐view abdominal‐pelvic imaging in multicenter studies. Issue 1 (21st December 2015) - Winfield, Jessica M.; Collins, David J.; Priest, Andrew N.; Quest, Rebecca A.; Glover, Alan; Hunter, Sally; Morgan, Veronica A.; Freeman, Susan; Rockall, Andrea; deSouza, Nandita M.
Abstract : Purpose: To develop methods for optimization of diffusion‐weighted MRI (DW‐MRI) in the abdomen and pelvis on 1.5 T MR scanners from three manufacturers and assess repeatability of apparent diffusion coefficient (ADC) estimates in a temperature‐controlled phantom and abdominal and pelvic organs in healthy volunteers. Methods: Geometric distortion, ghosting, fat suppression, and repeatability and homogeneity of ADC estimates were assessed using phantoms and volunteers. Healthy volunteers (ten per scanner) were each scanned twice on the same scanner. One volunteer traveled to all three institutions in order to provide images for qualitative comparison. The common volunteer was excluded from quantitative analysis of the data from scanners 2 and 3 in order to ensure statistical independence, giving n = 10 on scanner 1 and n = 9 on scanners 2 and 3 for quantitative analysis. Repeatability and interscanner variation of ADC estimates in kidneys, liver, spleen, and uterus were assessed using within‐patient coefficient of variation (wCV) and Kruskal–Wallis tests, respectively. Results: The coefficient of variation of ADC estimates in the temperature‐controlled phantom was 1%–4% for all scanners. Images of healthy volunteers from all scanners showed homogeneous fat suppression and no marked ghosting or geometric distortion. The wCV of ADC estimates was 2%–4% for kidneys, 3%–7% for liver, 6%–9% for spleen, and 7%–10% for uterus. ADC estimates in kidneys, spleen, and uterus showed no significant difference between scanners but a significant difference was observed in liver ( p < 0.05). Conclusions: DW‐MRI protocols can be optimized using simple phantom measurements to produce good quality images in the abdomen and pelvis at 1.5 T with repeatable quantitative measurements in a multicenter study.